Safe Autopsy Procedures for COVID-19: Experience of One Research Center - Cline, Madison P; Stewart, Analisa M; Intorcia, Anthony J; Walker, Jessica E; Nelson, Courtney M; Arce, Richard A; Glass, Michael J; Vargas, Daisy; Qiji, Sanaria H; Borja, Claryssa I; Hemmingsen, Spencer J; Krupp, Addison N; et al. (medRxiv : the preprint server for health sciences, 2025)
In the early days of the 2019 coronavirus disease (COVID-19) pandemic, there were few published guidelines for safely performing autopsies of infected individuals. The limited information relied on assumptions that the risks would be similar to those of other primarily respiratory infections, but there remained a considerable number of uncertainties, particularly in regard to the potential for aerosol transmission. Despite these novel risks, it was crucial for our program to quickly gain more knowledge about this new pathogen by continuing to perform autopsies while concurrently mitigating the risk of infection to autopsy personnel. Between January 26, 2020, the date of the first confirmed COVID-19 case in Arizona, and February 28, 2022, the Arizona Study of Aging and Neurodegenerative Disorders and its Brain and Body Donation Program performed autopsies on 162 subjects, of which 36 tested positive for SARS-CoV-2 on FDA-certified PCR tests while 2 were undiagnosed. In response to the increasing case rate in Arizona, major changes to the autopsy protocol were initiated in mid-March 2020, piloted by the autopsy director. While the new protocols were evolving and being implemented, autopsies were restricted to the brain in order to eliminate exposure to highly infectious respiratory tract tissues. Whole-body autopsies were resumed on June 6, 2020, after implementation of new protocols, which included engineering, environmental, and procedural changes designed to limit the risk to autopsy personnel. Due to a reasonable assumption that aerosol transmission was possible or probable, a key protocol change was our usage of a simple method for containment of bone saw-generated aerosols during skullcap removal, by using a heavy-duty clear polyethylene bag sealed at the subject's neck and saw handle. Spinal cord removal was permanently suspended due to the challenges of containing the aerosols. During this reported time period, there were 94 COVID-19 autopsy exposures involving 19 staff members, with only 2 occurrences of a single autopsy team member testing positive for SARS-CoV-2, by an FDA-licensed PCR test, within 7 days of their participation in a SARS-CoV-2-positive autopsy. During this same time period, 9 autopsy personnel tested positive without this temporal proximity to autopsy participation. This suggests that our revised protocols, when adequately implemented, drastically reduces any enhanced risk of SARS-CoV-2 infection to autopsy personnel beyond the normal risk already established within the community. We therefore recommend the use of our protocol to other laboratories performing autopsies on subjects with health-threatening communicable conditions.